Urbanization is a main driver for the larval ecology of Aedes mosquitoes in arbovirus-endemic settings in south-eastern Côte d'Ivoire. - Julien B Z Zahouli; Benjamin G Koudou; Pie Müller; David Malone; Yao Tano; Jürg Utzinger (Public Library of Science (PLoS), 2017)
Failure in detecting naturally occurring breeding sites of Aedes mosquitoes can bias the conclusions drawn from field studies, and hence, negatively affect intervention outcomes. We characterized the habitats of immature Aedes mosquitoes and explored species dynamics along a rural-to-urban gradient in a West Africa setting where yellow fever and dengue co-exist.Between January 2013 and October 2014, we collected immature Aedes mosquitoes in water containers in rural, suburban, and urban areas of south-eastern Côte d'Ivoire, using standardized sampling procedures. Immature mosquitoes were reared in the laboratory and adult specimens identified at species level.We collected 6,159, 14,347, and 22,974 Aedes mosquitoes belonging to 17, 8, and 3 different species in rural, suburban, and urban environments, respectively. Ae. aegypti was the predominant species throughout, with a particularly high abundance in urban areas (99.374%). Eleven Aedes larval species not previously sampled in similar settings of Côte d'Ivoire were identified: Ae. albopictus, Ae. angustus, Ae. apicoargenteus, Ae. argenteopunctatus, Ae. haworthi, Ae. lilii, Ae. longipalpis, Ae. opok, Ae. palpalis, Ae. stokesi, and Ae. unilineatus. Aedes breeding site positivity was associated with study area, container type, shade, detritus, water turbidity, geographic location, season, and the presence of predators. We found proportionally more positive breeding sites in urban (2,136/3,374, 63.3%), compared to suburban (1,428/3,069, 46.5%) and rural areas (738/2,423, 30.5%). In the urban setting, the predominant breeding sites were industrial containers (e.g., tires and discarded containers). In suburban areas, containers made of traditional materials (e.g., clay pots) were most frequently encountered. In rural areas, natural containers (e.g., tree holes and bamboos) were common and represented 22.1% (163/738) of all Aedes-positive containers, hosting 18.7% of the Aedes fauna. The predatory mosquito species Culex tigripes was commonly sampled, while Toxorhynchites and Eretmapodites were mostly collected in rural areas.In Côte d'Ivoire, urbanization is associated with high abundance of Aedes larvae and a predominance of artificial containers as breeding sites, mostly colonized by Ae. aegypti in urban areas. Natural containers are still common in rural areas harboring several Aedes species and, therefore, limiting the impact of systematic removal of discarded containers on the control of arbovirus diseases.